Factors Influencing and Hindering Customers’ Adoption of Electronic Banking Services: Comparative Study between Saudi and Egyptian Banks Customers - Mohamed, Mamdouh (The Arab Journal of Administration, 2021)
The study aimed to identify the factors affecting and impeding the adoption of e-banking services in Saudi and Egyptian banks and to know the impact of demographic factors in the adoption of these services. The study population consisted of different customers of these banks, 384 questionnaires were distributed, of which 350 were analyzed by 91%. Research hypothesis were tested though using SPSS program. The results of the study showed that: There are differences in the attitudes of bank customers towards e-banking services, and that there is an effect of factors (availability, awareness of the e-banking services, speed of execution of transactions, cost of service, perceived benefits, confidence, ease of use, Security, self-ability) as factors influencing customer adoption of e-banking services, There is also an impact of factors (low security, low confidentiality, low customer awareness, slow Internet service, low confidence, frequent faults and errors, high cost, random spread of ATM sites, lack of comprehensive services, high risk, lack of legislations, non-proliferation of POS, and difficulty in using) as constraining factors for such services, There are differences between the attitudes of Saudi and Egyptian customers in these influential and obstructive factors. The study indicated that there is an effect on the demographic factors (age, occupation, monthly income, educational level) on Customer adoption of e-banking services represented in (ATM, POS, talking bank, home bank). The study recommended the importance of: the development of banking technology, the deployment of POS, the permanent availability of the service, spread of banking awareness of the benefits of the service, export confidence to the customer, the development of the Internet and fees reduction, support the self-capacity of customers, processing technical competencies to prosecute penetration and fraud, demanding more legislation and laws, Establishment of a risk management unit.